Effect of tumor budding and tumor infiltrating lymphocytes on prognosis of colorectal mucinous adenocancers - Fatmagul Kusku Cabuk; Damlanur Sakiz; Elif Eda Ozer; Zehra Sibel Kahraman (Medicine Science, 2019)
Mucinous adenocarcinoma (MAC) has a worse prognosis than do classical adenocarcinoma. Increased tumor budding (TB) and lower number of tumor infiltrating lymphocytes (TIL) negatively affect prognosis in classical adenocarcinoma. In this study, we investigated whether TB and TIL values influenced prognosis in patients with MAC. Forty-five patients diagnosed with MAC between 2011 and 2015 were included in the study. TB and TIL values of the patients were re-evaluated. In assessing TIL, lymphocytes that infiltrated the stroma and tumor were evaluated separately. The effects of these findings on the prognostic parameters and the disease-free survival (DFS) and overall survival (OS) were evaluated. The mean follow-up period was 26.07 months (min: 1 max: 82, SD:24.86), OS 28.04 months (min: 1 max: 82 SD:24.81). The results between TB and OS (p = 0.066) and DFS (p = 0.205) were not significant. The relationship between sTIL and OS (p = 0.367) and DFS (p = 0.949) was not significant. The relationship between iTIL and OS (p = 0.502) and DFS (p = 0.870) was not significant. The only significant difference between clinicopathological parameters and TB, sTIL, and iTIL was between grade and TB (p = 0.016). In terms of clinicopathologic parameters, stage with OS (p = 0.008) and DFS (0.016), lymph node metastasis with OS (p = 0.010) and DFS (0.008), LVI (lymph vascular invasion) with OS (p = 0.034) and DFS (p = 0.015), PNI (perineural invasion) and DFS (p = 0.007) was significant. In this study, the effect of TB and TIL on the prognosis of MAC was investigated. We found that these data did not correlate with the prognosis of the tumor and the prognostic parameters (LVI, PNI, lymph node metastasis, stage) in the staging system remained as the gold standard for predicting prognosis. [Med-Science 2019; 8(4.000): 896-900]